Implementation of Semester Examinations in the Digital Age, Opportunities and Challenges - Ida Martinelli; Nurhasanah Nasution; Nalil Khairiyah, (Journal of Communication in Scientific Inquiry (JCSI), 2024)
The demand to apply digital technology is a must for all elements of education in higher education. Almost all higher education tri-dharma activities are carried out using digital technology. The implementation of semester exams both online and offline is carried out along with the use of online learning media such as E-Learning, Classroom, Whatsapp, etc. There is also a special application for final assessment so that student test scores are calculated using the application. The problem is how prepared the resources in higher education are in using digital technology. This research aims to analyse the opportunities and challenges in conducting semester exams using digital technology. The research method uses qualitative methods with a post-positivism paradigm. Data were obtained from direct observation and in-depth interviews with relevant informants. The results of the study show that the opportunities for conducting semester exams using digital technology are the ease of implementation and the achievement of effectiveness and efficiency. While the challenge is the fulfilment of the factors that support the readiness of all resources so that the implementation of the semester exams can run smoothly.